THE EFFECT OF AI USE ON ENGLISH PROFICIENCY OF HIGH SCHOOL STUDENTS AT SMK TELKOM 2 MEDAN - Nia Putri Rahmadina; Bahagia Saragih; Dela Elysabet Sihite; Syeila Nurifki; Naomi Enjelika Hutagalung; Firna Pertiwi Saputri Hasibuan; Selfi Anjany (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the impact of artificial intelligence (AI) usage on the English proficiency of high school students at SMK Telkom 2 Medan. As AI-based tools such as chatbots, language learning apps, and automated writing assistants become increasingly integrated into students’ daily academic activities, they offer both potential benefits and challenges for language development. The research adopts a quantitative correlational approach, involving 40 students selected as participants. Data were gathered through questionnaires and English proficiency assessments, then analyzed using correlation and regression techniques. The results indicate a positive and statistically significant relationship between the use of AI tools and students’ English proficiency, particularly in improving vocabulary mastery, writing organization, and reading comprehension. Students also reported increased confidence when practicing English with AI assistance. However, the study also highlights potential drawbacks, such as over-reliance on AI-generated responses, which may limit critical thinking and reduce grammatical accuracy when students do not actively engage in the learning process. Overall, the findings suggest that AI can function as an effective supplementary tool in English learning when used thoughtfully and under proper guidance. This research contributes to the growing discussion on technology-enhanced language learning and offers practical insights for educators in integrating AI into classroom instruction in a balanced and pedagogically sound manner.